Characterizing Idioms: Conventionality and Contingency - Socolof, Michaela; Cheung, Jackie Chi Kit; Wagner, Michael; J. O'Donnell, Timothy (ACL 2022, 2022)
Idioms are unlike other phrases in two important ways. First, the words in an idiom have unconventional meanings. Second, the unconventional meaning of words in an idiom are contingent on the presence of the other words in the idiom. Linguistic theories disagree about whether these two properties depend on one another, as well as whether special theoretical machinery is needed to accommodate idioms. We define two measures that correspond to these two properties, and we show that idioms fall at the expected intersection of the two dimensions, but that the dimensions themselves are not correlated. Our results suggest that idioms are no more anomalous than other types of phrases, and that introducing special machinery to handle idioms may not be warranted.